Penetapan Kadar Asam Salisilat Pada Cream Anti Jerawat Yang Dijual Secara Online Shop Dan Di Apotek Menggunakan Metode Spektrofotometri UV-Vis Dan Alkalimetri - Subardi Bali; Larysa Fernenda (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Cream is a semi-solid preparation, using an emulsion containing not less than 60% water. Salicylic acid, an anti-acne and keratolic agent, is commonly administered topically. This study aims to analyze salicylic acid levels in anti-acne creams sold online and in pharmacies. Quantitative Testing uses UV -Vis Spectrophotometry and Alkalimetry. Quantitative testing using UV-Vis Spectrophotometry, there were 3 samples sold in pharmacies containing salicylic acid with sample levels A 1.568%, B 1.755%, C 0.895%, and samples sold online contained salicylic acid with sample levels D 0.151%. Alkalimetric quantitative testing, 3 samples sold in pharmacies contained salicylic acid with sample levels A 0.71%, B 0.36%, C 0.48%, and samples sold online contained salicylic acid with sample levels D 0, 42 %. Based on BPOM requirements, the permitted level of salicylic acid in cosmetics does not exceed 2%, so the anti-acne cream product meets BPOM requirements. The salicylic acid level was tested using Uv-Vis spectrophotometry and analyzed using Kruskal Wallis with a significance value of 0.00 (P0.05). It was said that the spectrophotometric method influenced determining the salicylic acid level from samples A – D. The salicylic acid level used alkalimetry. Homogeneity test with the Homogeneity of Variances test with a significance value of P (0.104 - 0.05) homogeneous data. Data were analyzed using ANOVA. The results of the One Way Anova test analysis show a significance value of 0.00 (P 0.05), so the salicylic acid levels of samples A – D carried out using alkalimetry show a significant difference between the 4 samples tested.